Effect of Nitrogen Levels on Use Efficiencies and Yield of Wheat at Bharatpur, Chitwan, Nepal - Ghimire, Prabin; Acharya, Ashok; Devkota, Chakra; Gairhe, Janma Jaya (The Geographic Base, 2021)
Improper nitrogen management and declining soil fertility are major constraints of wheat production in Nepal. Limited information is available on optimum nitrogen levels and use efficiencies. Therefore, a field experiment was conducted on November 2018 at the Inner Terai to determine the effect of nitrogen on yield and improve the nitrogen use efficiency of wheat. Levels of five nitrogen, 0 kg ha-1 (Control), 60 kg ha-1,80 kg ha-1, 100 kg ha-1 and 120 kg ha-1, were laid out in randomized complete block design (RCBD) with four replicates. Observations on growth parameters such as plant height (cm), tiller m-2 and yield attributing characteristics such as thousand grain weight (g), spike length (cm), and grain spike-1, were found to be highest at a nitrogen level of 120 kg ha-1. Nitrogen at 120 kg ha-1 increases the grain yield, straw yield and harvest index. The grain nitrogen concentration at 120 kg ha-1 was statistically similar to that at 100 kg ha-1 and 80 kg ha-1 while nitrogen uptake was highest (114. 833 kg ha-1) at 120 kg ha-1 and lowest in control. Agronomic use efficiency is highest at 100 kg ha-1 and lowest at 60 kg ha-1. The apparent fertilizer N 96 recovery percentage was high (49.62%) at 120 kg ha-1, which is statistically similar to 100 kg ha-1 (46.97%) and lowest (31.76%) at 60 kg ha-1. However, observing agro physiological efficiency and the nitrogen harvest index did not show any significant difference among treatments. The application of nitrogen at 120 kg ha-1 was required to produce the preferable yield and the nitrogen use efficiency traits.